Developing a nutrient recovery process for recovering nutrients in anaerobic digestate in low income countries - Rose, Christopher (Cranfield University, 2015)
It is estimated that 2.7 billion people worldwide are served by on-site sanitation facilities that require faecal sludge management. Anaerobic digestion is a treatment mechanism that can provide faecal sludge management, methane production and an effluent digestate rich in nutrients. However, there is a paucity of information regarding the composition of the input faecal sludge which hinders the advancement of anaerobic digestion treatment and downstream nutrient recovery together with a lack of knowledge as to how best to recover these output nutrients in a simple process. Following an initial review to collate composition data for fresh faeces and urine, practical studies examined the physical, biological and chemical composition and variation of four different types of faecal sludge from on-site sanitation facilities. Faecal sludge storage strongly influenced the biodegradability and methane production potential in subsequent anaerobic digestion. However, the high concentrations of ammonium observed in faecal sludge (520-1853 mg NH4-N L- 1 ) were highlighted as a key goal for nutrient recovery and the ability of biochar and clinoptilolite as natural adsorbents for ammonium recovery in a drying bed application were investigated through batch and dynamic studies using synthetic and real digestate. Batch tests observed ammonium uptake of 5 and 12.2 mg NH4-N/g for biochar and clinoptilolite respectively whilst under dynamic experimental conditions the most efficient operation for ammonium recovery was at the longest empty bed contact times (354 minutes), ensuring the maximum fertiliser value was obtained (60g NH4-N/kg clinoptilolite). Nevertheless, clogging occurred rapidly at the surface of the media bed (0.04 – 0.5 kg TS/m2 ), consequently a sacrificial sand layer (0.05 m) was included to increase the longevity of the nutrient recovery system (15 fold increase in TS application rates). It has been demonstrated that clinoptilolite can effectively be used as part of a sludge drying bed configuration to recover nutrients from digestate and the saturated media can be used directly as a fertiliser product or blended with the dried sludge to create a balanced nitrogen, phosphorus and potassium fertiliser product (5.9% NH4-N/ 4.2% P/ ≥6.0% K+ ).